PERAN TENAGA KEPENDIDIKAN DALAM MENINGKATKAN MUTU PELAYANAN SISWA - Cindy Audia Safira Putri; Evie Muliani; Rabiatul Adawiyah; Warman; Dwi Nugroho Hidayanto; Muhammad Amir Masruhim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of educational support staff in improving the quality of administrative services for students during the period 2020–2025, a time when schools experienced significant changes due to educational digitalization and the post-pandemic transition. Educational support staff hold a strategic function in ensuring the smooth delivery of administrative services such as student data management, new student admissions processes, academic information services, document archiving, and the facilitation of students’ learning needs. High-quality administrative services have a direct impact on the effectiveness of the learning process and the overall student experience at school. Using a qualitative approach, data were collected through interviews, observations, and document analysis to describe how educational support staff provide services that are fast, accurate, and responsive. The findings indicate that the role of support staff has strengthened through the use of information technology, which streamlines service workflows, although challenges remain in digital literacy, limited facilities, and uneven workload distribution. This study highlights the importance of enhancing staff competencies, strengthening digital-based administrative management systems, and ensuring policy support from schools to create more effective and higher-quality services for students.